Efektifitas Terapi Aroma Terapi Lavender terhadap Pengurangan Nyeri Persalinan Kala 1 Fase Aktif di Puskesmas Sentani Kabupaten Jayapura - Wijayanti, Ika (Journal of Midwifery Science: Basic and Applied Research, 2025)
Childbirth is something that is experienced by every woman who wants to remove the fetus from her womb. One thing that often accompanies this is pain. Pain during labor can be distinguished based on type, duration and intensity. Pain during labor can cause fatigue or weakness which can ultimately result in fetal distress, even death in the mother. In general, there are two ways to overcome pain during labor, namely by using pharmacological and non-pharmacological methods. The use of pharmacological methods reduces labor pain physiologically, but the psychological and emotional conditions of the mother will be neglected, while non-pharmacological methods are effective without adverse side effects and can increase satisfaction during labor because the mother can control her feelings and strength. some non-pharmacological methods for reducing pain are the use of lavender aromatherapy. This study aims to determine the effectiveness of lavender aromatherapy on reducing labor pain during the first active phase at the Sentani Health Center, Jayapura Regency. This study is a quasi-experimental study (Quasy Experiment) with a one group pretest-posttest design. The population in the study were all mothers giving birth in the Active phase at the Sentani Health Center, Jayapura Regency and the sample used was 15 mothers giving birth using the Non Probability Sampling technique with the "Accidental Sampling" approach. Results: there was a significant effect between pain intensity before and after being given lavender aromatherapy in mothers giving birth in the first stage of the active phase with a p value of -0.000 (, 0.05).